Implementation of Data Mining to Predict Stocks of Goods Using the Apriori Algorithm at Mom's Kitchen Bakery - Ruminse Situmorang; Fricles Ariwisanto Sianturi (Institute of Computer Science (IOCS), 2020)
The application of the Apriori Data Mining Algorithm in predicting stock items can be used to predict what types of goods or brands should be owned or what stocks are right for use in Mom's Kitchen bakery. By utilizing software that is designed or a system that has been made to predict the stock of goods at Mom's Kitchen bakery is one of the right ways to find out what customers are interested in using the Apriori algorithm. The results of this study are, companies can more easily provide products that customers want more based on the stock that has been provided. The system built is web-based using php with MySQL database.